Brand value analysis of brand equity in the new Solo City logo - Yudhanto, Sigied Himawan; Setyawan, Alfan; Prayoga, Dedy Eka Timbul; Muttaqin, Hermansyah; Widyamurti, Nidyah; Risdianto, Faizal (PRofesi Humas, 2023)
Background: This article analyzes the factors that affect brand equity in the search for brand value in the new visual logo Solo city, which functions as part of city branding. Purpose: The purpose of this study is to present four factors of brand equity. These four factors are what determine the search process, namely brand awareness, brand association, perceived quality, and brand loyalty and their implementation of the new visual logo of the city based on the perceptions put forward by residents of Solo could act as a parameter for measuring the effect value of the new logo as part of city branding process of Solo city. Methods: This research uses quantitative methods based on a questionnaire with 120 respondents; the test results were carried out using the Cronbach Alpha method (SPSS). by Brand Loyalty factors, marketing results, and brand awareness. Conclusion: This study also shows that there are significant differences in the results of the assessment, namely, the Brand Value factor, as thefactor that has the most influence in between supporting elements of the city of Solo, such as the municipal government, stakeholders, and residents. Implications: The results in the conclusion of model hypothesis testing show that variables of H1 to H6 are accepted. The results of this study form the basis of delivering recommendations and have implications of using logos as promotions and contributing to increasing the brand image of Solo.